Rancang Bangun Sistem Informasi Penyewaan iPhone Berbasis Web Menggunakan PHP Native dan MySQL (iRentPhone) - Wining Zulham Ramzi Akbar; Jordy Carlo; Niken Harsanti (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
An iPhone rental business requires well-organized records of device units, renters, transactions, and revenue reports to ensure that its services do not rely solely on manual documentation. This study aims to design and develop a web-based iPhone Rental Information System named iRentPhone as an operational management platform for administrators. The system was developed using native PHP, MySQL, HTML, CSS, JavaScript, and XAMPP as the local server environment. This study employed a descriptive research method and adopted the waterfall model for system development, consisting of requirements analysis, system design, implementation, testing, and evaluation. The main features of the system include administrator login, a dashboard displaying summary statistics, iPhone data management, renter data management, rental transactions, data search, reporting, and report printing. Functional testing using the black-box testing approach showed that each main feature was able to receive input, process data, and generate outputs according to the administrator’s requirements. The transaction interface was designed to emphasize payment information and transaction history, distinguishing it from the renter data page, which focuses on customer identity. The iRentPhone system helps make administrative processes more structured, accelerates data retrieval, and facilitates the preparation of rental reports. Keywords: information system, iPhone rental, native PHP, MySQL, web application. Abstrak Usaha penyewaan iPhone membutuhkan pencatatan data unit, data penyewa, transaksi, dan laporan pendapatan yang rapi agar pelayanan tidak hanya bergantung pada catatan manual. Penelitian ini bertujuan merancang dan membangun Sistem Informasi Penyewaan iPhone berbasis web bernama iRentPhone sebagai media pengelolaan operasional oleh admin. Sistem dikembangkan menggunakan PHP Native, MySQL, HTML, CSS, JavaScript, serta XAMPP sebagai lingkungan server lokal. Metode penelitian yang digunakan adalah metode deskriptif dengan pengembangan sistem model waterfall, meliputi analisis kebutuhan, perancangan, implementasi, pengujian, dan evaluasi. Fitur utama yang dihasilkan mencakup login admin, dashboard dengan statistik ringkas, pengelolaan data iPhone, data penyewa, transaksi penyewaan, pencarian data, laporan, dan cetak laporan. Hasil pengujian fungsional menggunakan pendekatan black-box menunjukkan bahwa setiap fitur utama dapat menerima masukan, memproses data, dan menghasilkan keluaran sesuai kebutuhan admin. Tampilan transaksi dirancang dengan fokus pada informasi pembayaran dan riwayat transaksi, sehingga dibedakan dari halaman data penyewa yang berfokus pada identitas pelanggan. Sistem iRentPhone membantu proses administrasi menjadi lebih terstruktur, mempercepat pencarian data, serta memudahkan penyusunan laporan penyewaan. Kata Kunci: sistem informasi, penyewaan iPhone, PHP Native, MySQL, aplikasi web.